KRUENG BRAYEUN'S POTENTIAL AS A RAW SOURCE OF DRINKING WATER FOR BANDA ACEH CITY AND ACEH BESAR DISTRICT IN ATTAINING SDGS (SUSTAINABLE DEVELOPMENT GOALS) - Yeggi Darnas (FKIP USK, 2021)
This study aims to analyze the potential of krueng brayeuen as a raw source of drinking water for the city of Banda Aceh and Aceh Besar district. Data was collected through document analysis and analysis of water samples taken from 5 different points in the Krueng Brayeuen watershed. Water quality analysis includes metal content of Fe, Mn, ammonia content, Total Dissolved Solid (TDS), and organic matter content. While other qualities include color, odor, taste, chlorine content, and others. The results showed that the water discharge of krueng brayeuen every year showed a promising value to be used as a source of raw water. The results of the water quality test showed that the water in Krueng Brayeuen was tasteless, colorless and odorless. Testing of all other water parameters such as iron content, Mn content, ammonia content and organic matter content met the drinking water standards in general where the levels were still below the threshold set by PP. 22/2021. Based on the results of the analysis of water quality and contamination, it can be concluded that krueng brayeuen water is very suitable to be used as a raw source of drinking water